Jejak Sejarah Kesehatan Mental : Dari Prasejarah Hingga Era Kontemporer - Cheirunnisa Gunawan; Nasichah Nasichah; Mochamad Azmi Rizkulloh (The Journal General Health and Pharmaceutical Sciences Research, 2023)
The research aims to explain the history of mental health from pre-historic times to the contemporary era. The research focus involves the analysis of empirical factors, paradigm shifts, and the evolution of approaches to the treatment of mental disorders. The research method used is descriptive qualitative, allowing researchers to deepen historical concepts of mental health and analyze their development. Data was obtained through literature reviews from previous research and analysis of reference books. Relevant information is drawn from journal conclusions and book summaries to form a comprehensive understanding of the historical footprint of mental health. As a result of research from journals and books, it can be concluded that the history of the development of mental health has involved significant changes in the paradigm of treating mental disorders. Starting from the pre-scientific era with the concepts of animism and naturalism, to the transition to the modern era which marks the peak of scientific development in the field of mental health. With this shift, the history of mental health reflects the evolution of society's view of mental disorders from mystical beliefs to modern scientific understanding. This research summary provides in-depth insight into how the evolution of mental health concepts has influenced approaches and treatments in society.